Prediagnostic Plasma IgE Levels and Risk of Adult Glioma in Four Prospective Cohort Studies - Federico C. F. Calboli; David G. Cox; J. E. Buring; J. Michael Gaziano; Jie Ma; Meir J. Stampfer; W. C. Willett; Shelley S. Tworoger; David J. Hunter; Carlos A. Camargo; Dominique S. Michaud (2011)
Results for women are based on the two female cohorts: Nurses' Health Study (NHS) and Women's Health Study (WHS).Results for men are based on the two male cohorts: Health Professionals Follow-up Study (HPFS) and Physicians' Health Study (PHS).Conditional logistic regression was used to analyze the matched nested case-control dataset after stratifying data by sex.CI = confidence interval; OR = odds ratio.† Total IgE levels were measured using the Pharmacia Diagnostics AB UniCAP fluorescent immunoassay; cut points were based on clinically defined cut points.Respiratory allergen-specific IgE was measured using the ImmunoCAP Phadiotop and food allergen-specific IgE was measured using a mixed food allergen assay from Pharmacia Diagnostics AB; recommended cut points were provided by Pharmacia Diagnostics AB. ‡ ORs for continuous variable (for increase by 1 ln total IgE).